INVESTIGATING THE FREQUENCY OF OCCUPATIONAL EXPOSURE IN DENTISTRY STUDENTS OF AHVAZ JUNDISHAPUR UNIVERSITY OF MEDICAL SCIENCES IN SOUTHWEST OF IRAN - Gilavand, Abdolreza; Shooriabi, Mohammad; Malakootian, Mehrnoosh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: In spite of great developments in infection control during recent years, many problems are still seen at the level of faculties, private, and public hospitals. Therefore, this research was carried out to evaluate the frequency of occupational exposure in dentistry students of Ahvaz Jundishapur University of Medical Sciences, Southwest of Iran. Methods: This study was conducted using a descriptive and cross-sectional method in 2016. The population of the study included all the 124 dentistry students graduated from Ahvaz Jundishapur University of Medical Sciences (AJUMS), southwest of Iran, who started their clinical education. The data were collected through a researcher-developed questionnaire and were analyzed using SPSS 22 software. Results: A total of 84 (67.7%) of the participants were male and 40 (23.3%) were female. Of all the participants, 54.8% of the students had no occupational exposure, 17.9% had needle stick experience, 17.9% of them had splash exposure, and 8.9% had a history of exposure to both needlestick acid and patient discharge. In the current research, no significant relationship was found between job exposure and age, gender, and marital status (p<0.05). However, a significant relationship was found between occupational exposure, year of admission to university, academic semester, and educational environment (p<0.05). Conclusion: Given the relatively high prevalence of occupational exposure in students, the development of prevention and exposure to occupational protocols and requiring students to comply with these protocols in clinical dentistry environments is recommended.